Vaccine adjuvant platform and fluorescence imaging of amphiphilic γ-PGA-IMQ-LA-FL conjugates. Issue 5 (10th February 2022) - Yin, Wenzhu; Xuan, Dechun; Deng, Bihua; Zhou, Mingxu; Ma, Fang; Zhang, Jinqiu; Lu, Yu
Abstract : A new amphiphilic polymer FIP provided a novel protein-based vaccine delivery platform, which was capable of inducing strong humoral and cellular immunity for effective vaccine prevention with acceptable safety. Abstract : Adjuvants have proven to be integral components in most vaccines for promoting appropriate immune responses at both innate and adaptive levels. Imiquimod (IMQ, R837), an agonist for Toll-like receptors 7 (TLR7), is a potent molecular activator of the innate immune system and has been developed as an adjuvant for immunotherapy. However, due to its pharmacokinetic profile, IMQ may induce strong local and systemic inflammatory reactions and is poorly tolerated. To overcome these hurdles, herein, we conjugate IMQ and lauryl alcohol (LA) to the backbone of biodegradable poly (γ-glutamic acid) (γ-PGA) to prepare an amphiphilic polymer (shortened to γ-PGA-IMQ-LA) with improved stability and biodistribution of IMQ. In order to investigate the distribution of the amphiphilic polymer in vitro and in vivo, fluorescein was grafted to the lateral chain to synthesize fluorescent-labeled γ-PGA-IMQ-LA-FL (shortened to FIP). The novel amphiphilic FIP polymer was characterized via 1 H NMR, FI-IR, UV-vis, fluorescence spectra and zeta potential. Using ovalbumin (OVA) as a model antigen and FIP as an adjuvant for immunization, the formulations of FIP + OVA in different dosages could significantly promote the production of OVA-specific IgG in mice and prolong immune responses with acceptable safety.